The Relationship of Some Biomechanical Variables And The Level Of Layup Performance In Premier League basketball players season (2016-2017) - Ahmed, Hamid; Faris, Laith (Journal of Physical Education, 2018)
The Relationship of Some Biomechanical Variables And The Level Of Layup Performance In Premier League basketball players season (2016-2017)The researchers noticed variations in the performance of the basic offensive skill that ends with layup shooting or in the motor sequence of complex skill with the lack of accuracy under speed pressure, which reflects the reality of the training process itself. The study aimed at identifying the relationship of some biomechanical variables with the level of performing offensive skills that ends with layup shot in six basketball teams of the Iraqi basketball primer league. The researchers used the descriptive method. The subjects were (48) players from six clubs from the Premier League basketball for the season (2016-2017). The data was collected and treated using proper statistical operation to conclude that there is a relationship between some biomechanical variables and the level of performing layup shooting. Finally they recommended paying attention to teaching aids in developing basic skills in basketball.